ANALISIS PERKIRAAN TDOA MENGGUNAKAN ALGORITMA LMS ADAPTIF PADA PELACAKAN PAUS LODAN - , ANDRIYAN PERMANA; Dr. Agfianto Eko Putra, M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Research on TDOA estimation in sperm whale tracking has been done by Kandia et al. (2008) that use the Teager - Kaiser operator in improving estimation accuracy for TDOA value using adaptive LMS algorithm on sperm whale tracking. However, further studies have not been performed on the right convergence factor (Î¼) (fast and accurate) in TDOA estimation using adaptive LMS algorithm for sperm whale tracking. Therefore, will be analyzed TDOA estimation using adaptive LMS algorithm for sperm whale tracking with the variation of Î¼. In this study, as a reference to determine the right value of Î¼, is used to study the results of tracking whales Kandia et al . (2009) . TDOA estimation using Adaptive LMS algorithm was first published by Benesty (2000). The approach taken is based on the estimation of the impulse responses from source to receivers. In the adaptive LMS algorithm the function updates the value of the coefficient with the error function which is already known and Î¼ as adaptation step. TDOA values obtained from the difference between the two impulse response distances where one of them has been initialized. From the research results the change value of Î¼ affect the speed of TDOA estimation using the LMS adaptive algorithm. However, the wrong values of Î¼ lead to inaccurate sperm whale tracking results. From this research obtained the best value of Î¼ for TDOA estimation using the LMS adaptive algorithm for sperm whale tracking is 0.01 .